El círculo de las calabazas : historia de un huerto - Levenson, George (Tricycle Press, 2002)
Rhyming text and photographs follow a pumpkin patch as it grows and changes, from seeds to plants to pumpkins ready to harvest, to jack-o-lanterns and then to seeds again.